Comparison of the Properties of the Handwriting Speed Test (HST) and Detailed Assessment of Speed of Handwriting (DASH): An Exploratory Study. (15th March 2017) - Francis, Anna; Wallen, Margaret; Bundy, Anita
ABSTRACT: Background: Handwriting speed is an important component of students' ability to adequately express their ideas, knowledge and creativity in a timely and effective manner. Aims: Psychometric properties of the Handwriting Speed Test (HST) and Detailed Assessment of Speed of Handwriting (DASH) and accuracy of the norms for identifying current Australian students with handwriting speed difficulties were examined. Methods: An exploratory, cross-sectional study was conducted involving students, with and without handwriting difficulties, in Years 3–12 (mean age: 12.0 yrs, SD = 3.0 yrs; range = 7 to 18 yrs) in New South Wales (NSW; Australia). Participants were recruited through occupational therapists and schools. Students completed the HST and all DASH subtests. Results: Thirty-two students with, and 139 students without, handwriting difficulties participated. Intra-rater and inter-rater reliability were found to be excellent; sensitivity was low and specificity high for the HST and DASH. No significant differences were found between test scores and normative data for students without handwriting difficulties (year/age groups with n > 10). Conclusions: The HST and DASH are reliable assessments of handwriting speed. Further research is required into discriminant validity of the HST and DASH and need for updated norms.